(untitled) (AmeriQuests, 2015)
The two articles presented here are part of a larger project hosted by the W.T. Bandy Center for Baudelaire and Modern French Studies at Vanderbilt University, Nashville, TN. They treat the influence of the work of Baudelaire in South America.